2018
DOI: 10.1001/jama.2018.11597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Strategy of a Supraglottic Airway Device vs Tracheal Intubation During Out-of-Hospital Cardiac Arrest on Functional Outcome

Abstract: ISRCTN Identifier: 08256118.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
268
2
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 350 publications
(290 citation statements)
references
References 32 publications
5
268
2
15
Order By: Relevance
“…Based on the variability of individual intubation experience among paramedics in this single EMS, the results cannot be transferred to another EMS. Furthermore, our study was conducted over 4 years and there has possibly been an increase in SGA use by paramedics, because more recent studies indicated that SGAs could be equivalent or better than ETI [28,29]. This might have also an effect on the small number of cases in the whole investigation period.…”
Section: Limitationsmentioning
confidence: 99%
“…Based on the variability of individual intubation experience among paramedics in this single EMS, the results cannot be transferred to another EMS. Furthermore, our study was conducted over 4 years and there has possibly been an increase in SGA use by paramedics, because more recent studies indicated that SGAs could be equivalent or better than ETI [28,29]. This might have also an effect on the small number of cases in the whole investigation period.…”
Section: Limitationsmentioning
confidence: 99%
“…In the ED, up to 40% of intubations were carried out in patients with cardiac arrest . Although the best intubation strategy during cardiopulmonary resuscitation (CPR) has not been established, intubation is considered the definitive method to secure the airway . However, the conditions unique to this population, for example, continuous chest compression during CPR and regurgitation, successful emergency airway management is a challenge.…”
Section: Special Circumstance: Cardiac Arrestmentioning
confidence: 99%
“…In this paper, we summarize the rationale for, results of, and lessons from the Pragmatic Airway Resuscitation Trial (PART), the AIRWAYS-2 trial, and the Cardiac Arrest Airway Management (CAAM) trial. [6][7][8]…”
Section: Introductionmentioning
confidence: 99%